Design Optimization of Car Tire Noise - Ekaputra, Adi
The enforcement of many regulations encourages car tire industries to design their products that comply to certain environmental standards, such as UN ECE R117 standard in which specifies the tire noise value limit, rolling resistance, and wet grip. In order to face the challenge, tire industries have to develop a more effective and efficient method to design tires that comply to various needs and standards with low design cost. This final project research focused on the design optimization of tire noise level using Knowledge Based Design methodology. From the input-output database of tread pattern influence to noise, an approximate metamodel equation is created and will be used as the objective function for the optimization using Genetic Algorithm. Optimization process has been carried out on a number of parameters, i.e. groove width, groove depth, offset, sipe width, and sipe angle, based on noise minimization with certain criteria as the constraints, namely hydroplaning, grip ability, and both. The overall optimization process results in optimum tread pattern design with the following noise levels: 2.2009, 16.0747, 33.1104, and 27.207 dB(A) for the design target of: absolute minimum noise, minimum noise with hydroplaning ability, minimum noise with grip ability, and minimum noise with hydroplaning and grip ability, respectively.